Clinical trial enrollment at a rural satellite hospital during COVID-19 pandemic. Issue 1 (8th April 2021) - Sedhai, Yub Raj; Sears, Melissa; Vecchiè, Alessandra; Bonaventura, Aldo; Greer, Joan; Spence, Kathryn; Tackett, Hilary; Turner, Juanita; Pak, Mary; Patel, Nimesh; Black, Mellisa; Wohlford, George; et al.
Abstract: Introduction: Controlled clinical trials (CCTs) have traditionally been limited to urban academic clinical centers. Implementation of CCTs in rural setting is challenged by lack of resources, the inexperience of patient care team members in CCT conductance and workflow interruption, and global inexperience with remote data monitoring. Methods: We report our experience during the coronavirus disease 2019 (COVID-19) pandemic in activating through remote monitoring a multicenter clinical trial (the Study of Efficacy and Safety of Canakinumab Treatment for cytokine release syndrome (CRS) in Participants with COVID-19-induced Pneumonia [CAN-COVID] trial, ClinicalTrials.gov Identifier: NCT04362813) at a rural satellite hospital, the VCU Health Community Memorial Hospital (VCU-CMH) in South Hill, VA, that is part of the larger VCU Health network, with the lead institution being VCU Health Medical College of Virginia Hospital (VCU-MCV), Richmond, VA. We used the local resources at the facility and remote guidance and oversight from the VCU-MCV resources using a closed-loop communication network. Investigational pharmacy, pathology, and nursing were essential to operate the work in coordination with the lead institution. Results: Fifty-one patients with COVID-19 were enrolled from May to August 2020, 35 (69%) at VCU-MCV, and 16 (31%) at VCU-CMH. Among the patients enrolled at VCU-CMH, 37.5% were female, 62.5% Black, and had a median age of 60 (interquartile range 56–68) years. Conclusion: Local decentralization of this trial in our experience gave rural patients access to a novel treatment and also accelerated enrollment and more diverse participants' representative of the target population.